2020
DOI: 10.1002/ejhf.1863
|View full text |Cite
|
Sign up to set email alerts
|

Mitral regurgitation, edge‐to‐edge valve repair and the left atrium: one step beyond the left ventricle?

Abstract: This article refers to 'Impact of left atrial diameter on outcome in patients undergoing edge-to-edge mitral valve repair: results from the German TRAnscatheter Mitral valve Interventions (TRAMI) registry' by C. Iliadis et al., published in this issue on pages 1202-1210.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…5 As correctly pointed out by Yu et al, along with medical therapy, also the use of device such as cardiac resynchronization therapy (CRT) and Mitra-Clip system have been shown to favour LA reverse remodelling with a beneficial impact on prognosis. 6,7 As reported by the authors, also previous analysis from the Multicenter Automatic Defibrillator Implantation Trial with Cardiac Resynchronization Therapy (MADIT-CRT) 6 study showed that reductions in LA volume with CRT-defibrillator (CRT-D) at 1 year were highly associated with reduction in LV volume, suggesting a cause-effect relationship. In this trial, most CRT-D patients experienced ≥20% reduction in LA volume, while the implantable cardioverter-defibrillator (ICD)-only group had a significantly lower LA response.…”
Section: Reply To the Letter Regarding The Article 'Clinical Implicat...mentioning
confidence: 68%
“…5 As correctly pointed out by Yu et al, along with medical therapy, also the use of device such as cardiac resynchronization therapy (CRT) and Mitra-Clip system have been shown to favour LA reverse remodelling with a beneficial impact on prognosis. 6,7 As reported by the authors, also previous analysis from the Multicenter Automatic Defibrillator Implantation Trial with Cardiac Resynchronization Therapy (MADIT-CRT) 6 study showed that reductions in LA volume with CRT-defibrillator (CRT-D) at 1 year were highly associated with reduction in LV volume, suggesting a cause-effect relationship. In this trial, most CRT-D patients experienced ≥20% reduction in LA volume, while the implantable cardioverter-defibrillator (ICD)-only group had a significantly lower LA response.…”
Section: Reply To the Letter Regarding The Article 'Clinical Implicat...mentioning
confidence: 68%